2015
DOI: 10.1002/prp2.127
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the compound action potentials of frog sciatic nerves by aroma oil compounds having various chemical structures

Abstract: Plant-derived chemicals including aroma oil compounds have an ability to inhibit nerve conduction and modulate transient receptor potential (TRP) channels. Although applying aroma oils to the skin produces a local anesthetic effect, this has not been yet examined throughly. The aim of the present study was to know how nerve conduction inhibitions by aroma oil compounds are related to their chemical structures and whether these activities are mediated by TRP activation. Compound action potentials (CAPs) were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 50 publications
5
24
0
1
Order By: Relevance
“…For local anesthetics, there was a correlation between potency and lipid solubility as measured by the octanol/water partition coefficient (Strichartz et al, 1990); however, this relationship was not seen for monoterpenes. Instead, their relative potency in reducing the CAP amplitude was monoterpene aldehydes≥alcohols≥ketones >> hydrocarbons (Ohtsubo et al, 2015). The relative potency of our EO components in inhibiting synaptic transmission was consistent with these studies of the CAP amplitude.…”
Section: Relationship To Local Anestheticssupporting
confidence: 80%
See 1 more Smart Citation
“…For local anesthetics, there was a correlation between potency and lipid solubility as measured by the octanol/water partition coefficient (Strichartz et al, 1990); however, this relationship was not seen for monoterpenes. Instead, their relative potency in reducing the CAP amplitude was monoterpene aldehydes≥alcohols≥ketones >> hydrocarbons (Ohtsubo et al, 2015). The relative potency of our EO components in inhibiting synaptic transmission was consistent with these studies of the CAP amplitude.…”
Section: Relationship To Local Anestheticssupporting
confidence: 80%
“…through VG Ca 2+ channels. Citral, carvone and limonene reduced the compound action potential (CAP) amplitude in frog sciatic nerve; citral was the most potent (IC 50 0.5 mmol l −1 ) followed by carvone (IC 50 1.4-2.0 mmol l −1 ), and limonene produced a slight reduction in CAP at 10 mmol l −1 (Kawasaki et al, 2013;Ohtsubo et al, 2015). This reduction in CAP amplitude presumably resulted from inhibition of VG Na + channels since a correlation between a reduction in CAP amplitude and VG Na + currents was demonstrated for the monoterpenes linalool and carvacrol (Joca et al, 2012;Leal-Cardoso et al, 2010).…”
Section: Citral Reduces Transmitter Release and Ca 2+ Influxmentioning
confidence: 99%
“…It was suggested that compounds with different chemical structures could inhibit nerve conduction possibly without TRP activation. In this direction, functional tests performed in the presence of TRPV1 or TRPA1 antagonists failed to demonstrate a role for TRPs in the pharmacological effects of linalool [20] or β-citronellol [21,22], two volatile compounds possessing the ability to activate TRPs [19,23]. Thus, the chances to obtain a positive result in experiments that combine α-terpineol and antagonists of TRPs under our experimental conditions appear small.…”
mentioning
confidence: 74%
“…Such findings raise the possibility that α-terpineol is a candidate to induce inhibition of nerve conduction by acting on TRP proteins. However, a recent study compared the inhibitory effects of α-terpineol and other volatile compounds on frog sciatic nerves [19]. It was suggested that compounds with different chemical structures could inhibit nerve conduction possibly without TRP activation.…”
mentioning
confidence: 99%
“…CAP inhibitory actions similar to those of analgesic adjuvants and NSAIDs were seen by plant-derived compounds that are known to produce antinociception by their oral, intraperitoneal or intrathecal administration (see [257,258] for reviews). Thus, frog sciatic nerve CAPs were inhibited by plant-derived compounds whose IC 50 values were close to those of analgesic adjuvants and NSAIDs ( [27,[259][260][261]; see [262] for review). Carvacrol, thymol, citronellol, bornyl acetate, citral, citronellal and geranyl acetate had IC 50 values of 0.34, 0.34, 0.35, 0.44, 0.46, 0.50 and 0.51 mM, respectively, in reducing CAP peak amplitudes.…”
Section: Antinociceptive Plant-derived Compounds Inhibit Nerve Conducmentioning
confidence: 99%